Cell-free cryopreserved arterial allografts from multiorgan donors: a new strategy to fabricate artificial blood vessels suited for peripheral vascular surgery - Papadopulos, Francesca Marzia <1977> (Alma Mater Studiorum - Università di Bologna, 2012)
Critical lower limb ischemia is a severe disease. A common approach is infrainguinal bypass. Synthetic vascular prosthesis, are good conduits in high-flow low-resistance conditions but have difficulty in their performance as small diameter vessel grafts. A new approach is the use of native decellularized vascular tissues. Cell-free vessels are expected to have improved biocompatibility when compared to synthetic and are optimal natural 3D matrix templates for driving stem cell growth and tissue assembly in vivo. Decellularization of tissues represent a promising field for regenerative medicine, with the aim to develop a methodology to obtain small-diameter allografts to be used as a natural scaffold suited for in vivo cell growth and pseudo-tissue assembly, eliminating failure caused from immune response activation. Material and methods. Umbilical cord-derived mesenchymal cells isolated from human umbilical cord tissue were expanded in advanced DMEM. Immunofluorescence and molecular characterization revealed a stem cell profile. A non-enzymatic protocol, that associate hypotonic shock and low-concentration ionic detergent, was used to decellularize vessel segments. Cells were seeded cell-free scaffolds using a compound of fibrin and thrombin and incubated in DMEM, after 4 days of static culture they were placed for 2 weeks in a flow-bioreactor, mimicking the cardiovascular pulsatile flow. After dynamic culture, samples were processed for histological, biochemical and ultrastructural analysis. Discussion. Histology showed that the dynamic culture cells initiate to penetrate the extracellular matrix scaffold and to produce components of the ECM, as collagen fibres. Sirius Red staining showed layers of immature collagen type III and ultrastructural analysis revealed 30 nm thick collagen fibres, presumably corresponding to the immature collagen. These data confirm the ability of cord-derived cells to adhere and penetrate a natural decellularized tissue and to start to assembly into new tissue. This achievement makes natural 3D matrix templates prospectively valuable candidates for clinical bypass procedures === L’ischemia critica degli arti inferiori è una condizione morbosa che riduce gravemente il flusso sanguigno e mette a repentaglio la conservabilità dell’arto colpito. Il trattamento standard è rappresentato dal bypass femoro-popliteo. Per questo tipo di rivascolarizzazione ci si avvale di protesi sintetiche o di graft in vena. Un approccio alternativo è l'uso di tessuti vascolari nativi decellularizzati, dotati di maggiore biocompatibilità rispetto agli altri e presumibilmente ottimi modelli 3D per guidare la crescita di cellule staminali. Lo scopo di questa ricerca è sviluppare una metodologia per ottenere allograft di piccolo calibro cell-free da utilizzare come scaffold naturali compatibili con la crescita cellulare in vivo e il loro assemblaggio in pseudo-tessuti, eliminando fallimenti dovuti all’attivazione della risposta immunitaria. Materiali e metodi: Abbiamo isolato dal cordone ombelicale umano cellule mesenchimali. La caratterizzazione con tecniche di immunofluorescenza e molecolari ha rivelato un profilo staminale. La decellularizzazione di segmenti vascolari è stata effettuata utilizzando un protocollo, che associa shock ipotonico e l’utilizzo di detergenti ionici. Le cellule sono state seminate su cell-free scaffold utilizzando come carrier fibrina e trombina, dopo 4 giorni di coltura statica in DMEM sono stati posti per 2 settimane in un bireattore a flusso che mima il fisiologico flusso pulsatile cardiovascolare. Al termine della coltura dinamica, i campioni sono stati processati per analisi istologiche, biochimiche e ultrastrutturali. Risultati e discussione: L’analisi istologica ha mostrato una propensione delle cellule a aderire e penetrare nel tessuto. Inoltre la colorazione Sirius Red ha rivelato la neoproduzione fibre di collagene III dato confermato dall'analisi ultrastrutturale dalla quale è emersa la presenza di fibre di collagene di 30 nm, presumibilmente corrispondente al collagene immaturo. Questi dati confermano la capacità delle cellule ombelicali di ricellularizzare tessuti nativi cell-free. Questo risultato rende gli scaffold naturali decellularizzati validi candidati per interventi di bypass.